Islam dalam Serat Kapracayan - Nurhayati, Arifah; Ekowati, Venny Indria; Rokhimah, Fitri; Nurhidayati, Nurhidayati (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
The Serat Kapracayan manuscript is one of the manuscripts that contains Islamic religious teachings. This manuscript is interesting to research because it contains texts of Islamic beliefs based on Javanese thought. This research aims to explain the teachings of Islamic beliefs written in the Serat Kapracayan text and explain the harmony between Islamic teachings in the Serat Kapracayan text and the Al-Qur'an. The methods used in this research are descriptive research methods and modern philological research methods. The data collection technique uses philological research steps, namely (1) manuscript inventory, (2) manuscript description, (3) text transfer, (4) text editing, (5) text translation. The content analysis method uses descriptive analysis techniques. The result of this research is an explanation of the contents of the Serat Kapracayan text which contains the teachings of Islamic beliefs. The Islamic belief teachings written in the Serat Kapracayan and in harmony with the Al-Qur'an are belief in Allah, prophets, destiny, angels, the book of the Al-Qur'an, and the concept of eschatology (doomsday, heaven and hell).